2018
DOI: 10.1016/j.gore.2018.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Extraovarian sex cord tumor with annular tubules discovered arising from a leiomyoma

Abstract: BackgroundSex cord tumors with annular tubules (SCTAT) are a rare (2%) subtype of ovarian sex cord-stromal tumor. SCTATs are usually cured at time of diagnosis by surgical resection with an oophorectomy. SCTATs have a 100%(disease related) five-year survival. One third of SCTAT tumors are associated with Peutz-Jeghers syndrome. Literature review discovered only two published cases of extra-ovarian SCTAT. Due to the rarity there is no standard treatment for extraovarian SCTATs.CaseA 39-year-old para-1 female wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Qian et al ( 5 ) demonstrated a 100% survival rate in 5 year, while their median progression-free survival time was 97.8 months by a retrospective study, which showed the overall good prognosis. The annual surveillance for 8–10 years with or without ultrasound and tumor makers serology (estradiol and/or progestin) depending on clinical suspicion was recommended ( 4 , 22 ). In our case, regular supervision has persisted in 2 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qian et al ( 5 ) demonstrated a 100% survival rate in 5 year, while their median progression-free survival time was 97.8 months by a retrospective study, which showed the overall good prognosis. The annual surveillance for 8–10 years with or without ultrasound and tumor makers serology (estradiol and/or progestin) depending on clinical suspicion was recommended ( 4 , 22 ). In our case, regular supervision has persisted in 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…SCTAT is reported that about one third of patients experience Peutz-Jeghers syndrome (PJS) with mucocutaneous pigmentation in special locations and gastrointestinal tract polyposis, whose form is usually benign and has excellent prognosis through surgery. However, SCTAT without PJS may have a 15–20% malignancy rate and malignant behavior with metastases might be examined in approximately 20% of patients ( 4 ), which is a most common phenomenon in women of reproductive age. The tumors both may express the hyperestrogenic manifestations, regardless of the clinical form.…”
Section: Introductionmentioning
confidence: 99%
“…SCTAT, representing 2% of all sex cord-stromal tumors, are considered very rare neoplasias (54). An increased progesterone production has been revealed in some cases (55).…”
Section: Endocrine Aspects In Femalesmentioning
confidence: 99%
“…This risk may approach a 20-fold increase over the general population if all organs are considered, although the increased risk for any particular site is necessarily more modest. About three quarters of PJS cases occur in families, with the remainder resulting from new mutations or low penetrance variants 1,2 .…”
Section: Introductionmentioning
confidence: 99%